2015
DOI: 10.3233/bme-151530
|View full text |Cite
|
Sign up to set email alerts
|

Peroxynitrite induced fibrinogen site identification

Abstract: Abstract. An increasing number of peroxynitrite-mediated fibrinogen nitrifications have been associated with thrombotic diseases. However, few reports related to priority nitrified fibrinogen injury sites exist. In this paper, an improved method, which simulated the environment in vivo, was used to inspect the structural changes of fibrinogen treated with peroxynitrite and LC-MS/MS in order to investigate the fibrinogen injury sites. The SDS-PAGE results indicated that Ȗ subunits of Fg were vulnerable to oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Nitration of fibrinogen mainly affects tyrosine residues, resulting in the formation of 3-nitrotyrosine. 21,22 Also cysteine residues can be affected, resulting in the formation of 3-nitrocysteine (Figure 2).…”
Section: Nitrationmentioning
confidence: 99%
“…Nitration of fibrinogen mainly affects tyrosine residues, resulting in the formation of 3-nitrotyrosine. 21,22 Also cysteine residues can be affected, resulting in the formation of 3-nitrocysteine (Figure 2).…”
Section: Nitrationmentioning
confidence: 99%
“…fibrinogen β chain migrated at about 50, 40 and 37 kDa 74 , while in the studies of Luo et al . the mass of the β chain was determined at 52 kDa and the γ chain at 46 kDa 75 . The observed masses only slightly differ from the mass of the band determined by us (49.3 kDa, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Residue Y277 was also the most highly modified in our study, but Y135 was modestly nitrated at 14% for the highest treatment. Luo et al identified 15 nitrotyrosine sites in the  chain of which Y96, Y262, Y274, Y348, and Y363 were most susceptible, but did not quantify the extent of modification at specific residues (Luo et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Analyzing fibrinogen nitrated in vitro using peroxynitrite, Tang et al identified 26 different 3-nitrotyrosine sites across the three fibrinogen subunits, among a total of 39 tyrosine residues that were observed in the experiments [33]. Luo et al found that fibrinogen polypeptide  chain was nitrated in a concentration-dependent manner on exposure to peroxynitrite [34]. Analysis of the  chain determined that the extent of nitration of the identified 3-nitrotyrosine sites was directly proportional to the ratio ONOOto protein used, and overall, five susceptible nitration sites on that chain were identified.…”
Section: Introductionmentioning
confidence: 99%